Rhabdomyolysis due to nutritional supplements intake: Case report - Eduardo Segovia-Vergara; Daniela Veloso-Soto; Javiera Villota-Neumann; Javiera Morales-Burdiles (Apunts Sports Medicine)
Rhabdomyolysis is a condition characterized by the destruction of muscle cells and subsequent release of it's intracellular contents. It is typically asymptomatic, with moderate creatine kinase elevation. Severe cases can involve disseminated intravascular coagulation, liver failure, or acute kidney injury, with a mortality rate of up to 50 %. Nutritional supplements containing compounds such as synephrine, caffeine, and clenbuterol have been reported to precipitate rhabdomyolysis. This case describes a 26-year-old male who, after consuming a full jar of fat burners, developed severe abdominal pain, choluria, myalgias, and muscle weakness. He was diagnosed with rhabdomyolysis and acute renal failure, requiring intensive care unit admission. The unregulated use of nutritional supplements may be an underestimated risk factor for rhabdomyolysis, especially given the fact that many cases are underdiagnosed.